Ocena ryzyka uzależnienia od opalania w wybranej populacji kobiet w wieku 15-30 lat - Aneta Szczerkowska-Dobosz; Anna Ulatowska; Marta Stawczyk; Agnieszka Łakis (Termedia Publishing House, 2011)
Introduction. Excessive exposure to natural and artificial sources ofultraviolet radiation may lead to skin cancer, skin photoaging, as wellas tanning addiction.Objective. To evaluate sunbathing habits and risk of tanning addictionin a selected population of women.Material and methods. 496 women aged 15 to 30 years, studying atschools and universities with medical faculties and similar. On-line ordirect anonymous answers to questionnaire, which included questionsabout tanning preferences, knowledge about the danger of ultravioletradiation exposure, use of sunscreens, familial incidence of skin cancerand mCAGE questionnaire evaluating risk of tanning addiction.Results. 83.9% of respondents declared that they regularly tan. Amongthis group 18% had a positive result in the mCAGE questionnaire. Themost popular way of getting a tan was sunbathing (70.4%), but 62.7%of women had used a sunbed at least once in a lifetime and 26.6% didso regularly. The respondents using sunbeds were most often (20.2%)cosmetology students. A statistically significant correlation betweenduration of sunbed session and a positive result in the mCAGE questionnairewas observed. The biggest group of women (38%) thatdeclared they had never used a sunbed consisted of secondary schoolstudents.Conclusions. According to the results of our study, using natural andartificial sources of ultraviolet radiation is still popular among youngwomen. This population is also at risk of tanning addiction. Thereforewidespread educational programmes concerning health consequencesof excessive exposure to ultraviolet radiation are essential.